Effects of Neutrophil Extracellular Traps in Patients With Septic Coagulopathy and Their Interaction With Autophagy - Mao, Jia-Yu; Zhang, Jia-Hui; Cheng, Wei; Chen, Jian-Wei; Cui, Na (Frontiers in Immunology, 2021)
Introduction Neutrophil extracellular traps (NETs) act as a critical trigger of inflammation and coagulation. We hypothesized that NETs are associated with septic hypercoagulability. Materials and Methods In total, 82 patients admitted with sepsis in the Department of Critical Care Medicine of Peking Union Medical College Hospital were enrolled between February 2017 and April 2018. Clinical and hematological parameters and thrombotic or hemorrhagic events were recorded. Blood samples were obtained to assess biomarkers of NETs formation, including neutrophil elastase (ELA2) and citrullinated histone H3, and endothelial-derived biomarker syndecan-1. Autophagy levels and its regulation pathway was also examined to explore its interaction with NETs. Result Sepsis patients with disseminated intravascular coagulation (DIC) showed significantly higher levels of NETs formation [ELA2, 1247 (86-625) vs. 2039 (1544–2534), p <0.0001; H3, 140 (47–233) vs. 307 (199–415), p <0.0001]. NETs formation were independently associated with DIC risk [ELA2, OR 1.0028, 95% CI 1.0010–1.0045; H3, OR 1.0104, 95% CI 1.0032–1.0176] and mortality [ELA2, HR 1.0014, 95% CI 1.0004–1.0024; H3, HR 1.0056, 95% CI 1.0008–1.0115]. The area under the curve value for ELA2 in predicting DIC occurrence was 0.902 (95% CI, 0.816–0.957) and that of H3 was 0.870 (95% CI, 0.778–0.934). Furthermore, biomarkers of NETs formation, endothelial cells and autophagy exhibited a significant correlation [ELA2 and syn (r 0.5985, p < 0.0001), LC3B (r -0.4224, p < 0.0001); H3 and syn (r 0.6383, p < 0.0001), LC3B (r -0.3005, p 0.0061)]. Conclusion Increased NETs formation are significantly associated with sepsis-induced DIC incidence and mortality in sepsis patients, revealing a significant relationship with the autophagy pathway.